2003
DOI: 10.1161/01.cir.0000042704.37387.29
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Reflex in Heart Failure Patients

Abstract: Background-An important role of the increased stimulation of skeletal muscle ergoreceptors (intramuscular afferents sensitive to products of muscle work) in the genesis of symptoms of exertion intolerance in chronic heart failure (CHF) has been proposed. With the use of selective infusions and dietary manipulation methods, we sought to identify the role of H ϩ , K ϩ , lactate, and peripheral hemodynamics on ergoreflex overactivation. Methods and Results-Ten stable CHF patients (aged 67.9Ϯ2.5 years, peak oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 32 publications
(52 reference statements)
3
48
0
3
Order By: Relevance
“…V9E at any given V9CO 2 is typically increased. Contributory factors include: premature metabolic acidaemia (reflecting reduced O 2 delivery and/or utilisation) [146,147]; increased physiological dead space [4]; increased sympathetic system activation via mechano-or pressor-receptor stimulation in the exercising muscles [148][149][150][151][152] and, possibly, contributions from cardiopulmonary vagal and sympathetic reflexes [132,153,154]. Several studies have shown that breathing pattern in CHF is more rapid and shallow than in healthy controls at any given V9E [4,155,156].…”
Section: Ventilatory Abnormalitiesmentioning
confidence: 99%
“…V9E at any given V9CO 2 is typically increased. Contributory factors include: premature metabolic acidaemia (reflecting reduced O 2 delivery and/or utilisation) [146,147]; increased physiological dead space [4]; increased sympathetic system activation via mechano-or pressor-receptor stimulation in the exercising muscles [148][149][150][151][152] and, possibly, contributions from cardiopulmonary vagal and sympathetic reflexes [132,153,154]. Several studies have shown that breathing pattern in CHF is more rapid and shallow than in healthy controls at any given V9E [4,155,156].…”
Section: Ventilatory Abnormalitiesmentioning
confidence: 99%
“…As discussed, the mechanisms by which the mechanoreflex becomes exaggerated are presently unclear. Furthermore, a great deal of controversy exists regarding the contribution of the metabolic component of the EPR, because its activity has been reported to be both enhanced 14,15,21,34 and reduced 10,22 in response to exercise in CHF patients. As stated, it is plausible that initial reductions in peripheral blood flow result in an abnormal accumulation of exercise-induced metabolites in the muscle interstitium.…”
Section: Perspectivesmentioning
confidence: 99%
“…Therefore, even in terms of anatomical differentiation and regarding the physiological triggers, there is a degree of overlapping between mechano and metaboreceptors and more recent observations have challenged the classic description of these receptors as distinct structures 19,20 . Hence, we use the terms "ergoreceptors", which contemplate both types of afferences and "ergoreflex", which is the reflex triggered by both types of receptors 16,[21][22][23] .…”
Section: Mechanoreflex and Metaboreflex Controlmentioning
confidence: 99%
“…Thus, early acidosis occurs, as well as depletion of the high-energy compounds developed during the exercise, which, in turn, trigger other compensatory mechanisms. In normal individuals, these compensatory mechanisms would keep the skeletal muscle performance and cause the stimulation of several afferents, such as muscle ergoreceptors, which communicate with the brainstem on the level of muscle work -which triggers the ergoreflex 16,[21][22][23] .…”
Section: The Muscle Hypothesismentioning
confidence: 99%